2010
DOI: 10.1017/s1461145709991052
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behaviour is associated with expression and phosphorylation of CREB in human buffy coat

Abstract: Nicotine induces various acute und chronic pharmacological effects which can be long lasting and might lead to nicotine dependence. Nicotinic acetylcholine receptors (nAChRs) are involved in nicotine-induced phosphorylation of CREB (cyclic AMP response element-binding protein) in PC12h cells. Several studies, mainly done in animal models, report that CREB plays a role in anxiety, memory and substance abuse as well as in affective disorders. Information regarding nicotine effects on gene expression in humans in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The increased expression of both p‐CREB and p300/CBP was related to a direct effect of cigarette smoke exposure as assessed here in an in vitro model of bronchial epithelial cells. In this regard, it was previously demonstrated that nicotine activated ERK 1/2 thus leading to increased activation of CREB in peripheral blood of smokers (Lenz et al, , ). Since TLR4 activation promotes CREB activation (Mellett et al, ) and since cigarette smoke activates TLR4 and induces ERK 1/2 activation (Pace et al, ), it is conceivable that cigarette smoke activates CREB via TLR4 and ERK 1/2 activation in bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 91%
“…The increased expression of both p‐CREB and p300/CBP was related to a direct effect of cigarette smoke exposure as assessed here in an in vitro model of bronchial epithelial cells. In this regard, it was previously demonstrated that nicotine activated ERK 1/2 thus leading to increased activation of CREB in peripheral blood of smokers (Lenz et al, , ). Since TLR4 activation promotes CREB activation (Mellett et al, ) and since cigarette smoke activates TLR4 and induces ERK 1/2 activation (Pace et al, ), it is conceivable that cigarette smoke activates CREB via TLR4 and ERK 1/2 activation in bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 91%
“…Quantification of mRNA-SNCA mRNA was extracted from whole blood and reverse transcription was performed according to the manufacturer's instructions (RNeasy Mini Kit, Qiagen, Hilden, Germany; iScript cDNA Synthesis System, Bio-Rad, CA, USA) as previously described (Lenz et al 2010). Although DNase digestion is not required since RNeasy technology efficiently removes most of the DNA without DNAse treatment, we used the optional on-column DNase digestion with the RNase-free DNase Set (Qiagen, Hilden, Germany).…”
Section: Genetic Analysis Of Nacp-rep1 and In4mentioning
confidence: 99%
“…Nicotine has been shown to increase CREB activity in vitro and in vivo via several nAChR subtypes (Lenz et al 2010; Pluzarev and Pandey 2004; Hou et al 2004; Brunzell et al 2003; Hu et al 2002; Nakayama et al 2001) and activation of CREB seems to be essential for some behavioral responses to nicotine including conditioned place preference (Pascual et al 2009; Brunzell et al 2009). In contrast, melatonin signaling through Mtnr1a and/or Mtnr1b typically inhibits the protein kinase A signaling pathway, including reducing CREB activity via pertussis toxin sensitive G i proteins (Hardeland 2009).…”
Section: 4 Discussionmentioning
confidence: 99%